Urinary tract mycosis masquerading as renal papillary necrosis post-COVID: A case report (Indian Journal of Case Reports, 2024)
Urinary tract mycosis is more often seen in hospitalized patients than in community-acquired ones. Funguria is common but becomes invasive and life-threatening in immunosuppressed patients such as with diabetes mellitus, post-transplant, chronic antibiotic usage, cancer chemotherapy, and long-term steroids. In the last 2 years, the world has witnessed one of its worst pandemics with the COVID-19 infection, killing millions of people. Deaths have been due to the virus or secondary complications thereafter. Secondary fungal infections, especially those caused by mucormycosis, have been on the rise, the majority of which have been reported from India. The rhino-cerebral-pulmonary form is the most common, followed by isolated case reports of gastrointestinal, cutaneous, and musculoskeletal mucormycosis. Isolated renal and urinary tract mycosis in COVID-19 is an extremely rare association. We report a case of a middle-aged man with fairly well-controlled diabetes who received steroids for COVID-19 infection and, about 8 weeks later, presented with non-invasive mixed mycosis of the urinary tract that was managed conservatively without any surgical intervention.